High-Pass Filtering of Input Signals by the I(h) Current in a Non-Spiking Neuron, the Retinal Rod Bipolar Cell - Cangiano, Lorenzo (Public Library of Science, 2007)
Hyperpolarization–activated cyclic nucleotide–sensitive (HCN) channels mediate the I(f) current in heart and I(h) throughout the nervous system. In spiking neurons I(h) participates primarily in different forms of rhythmic activity. Little is known, however, about its role in neurons operating with graded potentials as in the retina, where all four channel isoforms are expressed. Intriguing evidence for an involvement of I(h) in early visual processing are the side effects reported, in dim light or darkness, by cardiac patients treated with HCN inhibitors. Moreover, electroretinographic recordings indicate that these drugs affect temporal processing in the outer retina. Here we analyzed the functional role of HCN channels in rod bipolar cells (RBCs) of the mouse. Perforated–patch recordings in the dark–adapted slice found that RBCs exhibit I(h), and that this is sensitive to the specific blocker ZD7288. RBC input impedance, explored by sinusoidal frequency–modulated current stimuli (0.1–30 Hz), displays band–pass behavior in the range of I(h) activation. Theoretical modeling and pharmacological blockade demonstrate that high–pass filtering of input signals by I(h), in combination with low–pass filtering by passive properties, fully accounts for this frequency–tuning. Correcting for the depolarization introduced by shunting through the pipette–membrane seal, leads to predict that in darkness I(h) is tonically active in RBCs and quickens their responses to dim light stimuli. Immunohistochemistry targeting candidate subunit isoforms HCN1–2, in combination with markers of RBCs (PKC) and rod–RBC synaptic contacts (bassoon, mGluR6, Kv1.3), suggests that RBCs express HCN2 on the tip of their dendrites. The functional properties conferred by I(h) onto RBCs may contribute to shape the retina's light response and explain the visual side effects of HCN inhibitors.